2004
DOI: 10.1182/blood-2003-10-3381
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of SU11248 with cytarabine or daunorubicin on FLT3 ITD–positive leukemic cells

Abstract: IntroductionAcute myeloid leukemia (AML) remains a difficult disease to treat. Patients typically respond to initial treatment with anthracycline and cytarabine-based induction chemotherapy, but most patients ultimately relapse and die of their disease. Internal tandem duplications (ITDs) of the juxtamembrane domain of the fetal liver tyrosine kinase 3 (FLT3) receptor tyrosine kinase are found in 20% to 30% of cases of de novo AML. FLT3 ITD mutations are the most common molecular abnormality associated with AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 43 publications
1
79
0
Order By: Relevance
“…Because of the ability to cause G 2 arrest, PKC412 is synergistic with drugs that are active in the G 2 /M phase, such as colchicine, in these cell lines. This may be an important advantage for the usage of PKC412 over other FLT3 inhibitors, because such effects have not been demonstrated with other FLT3 inhibitors (Levis et al, 2004;Yee et al, 2004). For the same reason, PKC412 may be antagonistic with drugs that synchronize target cells in late G 1 to early S phase, such as aphidicolin, in FLT3 mutation-negative leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the ability to cause G 2 arrest, PKC412 is synergistic with drugs that are active in the G 2 /M phase, such as colchicine, in these cell lines. This may be an important advantage for the usage of PKC412 over other FLT3 inhibitors, because such effects have not been demonstrated with other FLT3 inhibitors (Levis et al, 2004;Yee et al, 2004). For the same reason, PKC412 may be antagonistic with drugs that synchronize target cells in late G 1 to early S phase, such as aphidicolin, in FLT3 mutation-negative leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…They found that simultaneous exposure and sequential exposure with CEP-701 added after chemotherapeutic agents produced synergistic effects, whereas the reverse-sequence exposure resulted in an antagonistic effect. Yee et al 39 reported that SU11248 had synergistic effects with daunorubicin and cytarabine in several leukemic cell lines carrying FLT3 mutations. A similar tendency was observed in our study, although the FLT3 inhibitors used were different in each study.…”
Section: Discussionmentioning
confidence: 99%
“…SU11248, another FLT3 inhibitor, also was found to synergistically interact with Ara-C or Dox in vitro when given concurrently. 23 In contrast, pretreatment with ABT-869 followed by chemotherapy yielded an undesirable antagonistic effect. The antagonism observed could result from G 1 -phase cell cycle arrest and the removal of cells in the S-G 2 /M boundary by ABT-869, resulting in more cells under quiescent condition.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that combination of SU11248 with Ara-C or Dox exerted synergistic effects 23 and CEP-701 showed in vitro sequence-dependent synergistic cytotoxic effects on FLT3-ITD leukemia cells when combined with chemotherapy. 24 In this study, the sequence-dependent synergism was attributed to CEP-701-induced cell cycle arrest, and it was speculated that the sequential treatment first induced pro-apoptotic signals, then withdrew pro-survival signals.…”
Section: Introductionmentioning
confidence: 99%